Otorhinolaryngological manifestations in 61 patients with mucopolysaccharidosis. (August 2020) - Murgasova, Lenka; Jurovcik, Michal; Jesina, Pavle; Malinova, Vera; Bloomfield, Marketa; Zeman, Jiri; Magner, Martin
Abstract: Objectives: The mucopolysaccharidoses (MPS) are inherited lysosomal storage disorders with multisystemic and highly variable clinical manifestation. ENT symptoms are common and early signs of MPS. The most common ENT diagnoses are chronic/recurrent rhinosinusitis, acute otitis media, otitis media with effusion, hearing loss and airway obstruction. Methods: A single-centre retrospective chart review of 61 patients (36 M/25F) with different MPS subtypes (MPS I (n = 15), MPS II (n = 10), MPS III (n = 17), MPS IV (n = 15) and MPS VI (n = 4)) was conducted. The age of ENT presentation and frequency of ENT symptoms, surgeries and their distribution among MPS subtypes was studied. The relationship between ENT presentation, first ENT surgery and the age of diagnosis was also evaluated. Results: Median age at the first ENT manifestation was 2.8 years, median age at MPS diagnosis 4.1 years. The great majority of patients (90%) manifested at least one ENT diagnosis; often before the diagnosis of MPS (75%). Chronic/recurrent rhinosinusitis was the most prevalent ENT diagnosis (77%), followed by upper airway obstruction (65%) and hearing loss (53%). Chronic/recurrent rhinosinusitis was the first ENT symptom to appear (median age 2.2 years), followed by otitis media with effusion (3.7 years) and hearing loss (4.5 years). At least one ENT surgery was performed in 57% of patients; in 69% before MPS diagnosis was established. Median age of the first ENT surgery was 4.1 years. ENT symptoms and surgical procedures were earliest present in MPS II. Conclusions: Our study documents high and early occurrence of various otolaryngologic symptoms in MPS and thus highlights the role of ENT specialist in prompt diagnosis of these rare diseases and their long-term management. Highlights: Mucopolysaccharidoses are rare, highly variable multisystemic disorders. ENT symptoms are very common and often early signs of MPS patients. Suspicion of ENT specialists may be the first trigger towards establishing the diagnosis. An early diagnosis is critical for prompt introduction of therapy and long-term outcome.